2021
DOI: 10.1155/2021/1227876
|View full text |Cite
|
Sign up to set email alerts
|

Capparis spinosa Alleviates DSS-Induced Ulcerative Colitis via Regulation of the Gut Microbiota and Oxidative Stress

Abstract: Ulcerative colitis (UC) is a chronic inflammatory disease. Here, the potential effects of Capparis spinosa water extract (CSWE) on colonic histopathology, inflammation, and gut microbiota composition in dextran sulfate sodium (DSS) induced UC mice were evaluated. Our results showed that CSWE treatment improved the colonic histopathology of UC mice, increased the levels of tight junction protein gene ZO-1 and Occludin in intestinal epithelial cells, and inhibited the expression of proinflammatory cytokines (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Glucocapperin (methyl glucosinolate) is present above all in the buds and shoots and glucocleomine is present in the seeds and leaves. In the lipid fraction of the seeds, a high content of linoleic and oleic acid, sterols and tocopherols, aliphatic and triterpenic alcohol was detected [ 179 , 180 , 181 , 182 , 183 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glucocapperin (methyl glucosinolate) is present above all in the buds and shoots and glucocleomine is present in the seeds and leaves. In the lipid fraction of the seeds, a high content of linoleic and oleic acid, sterols and tocopherols, aliphatic and triterpenic alcohol was detected [ 179 , 180 , 181 , 182 , 183 ].…”
Section: Resultsmentioning
confidence: 99%
“…Classified among medicinal plants, CS is used in the remedy of diverse illnesses due to the flavonoids, alkaloids, and phenolic acids it contains. Studies have shown that CS fruits contain p-Coumaric acid (5.53 ± 0.01 mg/100 g DW), Ferulic acid (0.73 ± 0.00 mg/100 g DW), Catechin (0.91 ± 0.02 mg/100 g DW), Epicatechin (1.14 ± 0.01 mg/100 g DW), Rutin (17.12 ± 0.00 mg/100 g DW), Kaempferol (3.44 ± 0.01 mg/100 g DW), and Quercetin They have reported that after seven days of treatment, the expression IL-6, IL-1β, and TNFα was suppressed, and improvement was achieved in mice by reducing oxidative stress (26). In another study, a streptozotocin-induced diabetes model was established in rats by Jalali et al (27) and diabetic rats were treated with water extracts from CS fruits for 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [ 21 ] have reported that treatment with the aqueous C. spinosa fruit extract (200 and 400 mg/kg/day, for seven days) has anti-inflammatory effects in mice (n = 7) with ulcerative colitis, a chronic inflammatory disease. The tested extract reduced the expression of proinflammatory cytokines (TNF-α, IL-6, and IL-1β) and was found to have antioxidant properties.…”
Section: Biological Properties Of C Spinosamentioning
confidence: 99%